Propuesta de modelo de gestión y su incidencia en la conversión de empresa pública de A.A.P.P. y A.A.S.S. en el GADMCN del cantón Naranjal - Benavides Meléndres, José Manuel (2024)
In some Ecuadorian companies the concept of the continuous improvement process has become their quality policy, therefore, in order to consolidate the SGSST in the organization, implementing the PHVA cycle will establish the bases for the employees to solve in general any problem. Likewise, it is expected to methodologically contribute a contribution of continuous improvement to the reality that currently exists in our society, in such a way that it is a model that allows establishing a measurement parameter for the company. The research is developed in an organization located in Zone 8 of the Guayaquil Canton of the Guayas Province, with twenty years of experience in the market, dedicated to the design, construction, maintenance of infrastructures, specialized engineering services and other accessories, taking as measurement parameter the efficiency index (IE) of the Occupational Health and Safety Management System (SGSST) and the degree of perception that the insured and the employer have about its elements, for this it is necessary to strengthen the Management Administrative for the direction of the organization in the matter of risk prevention of the general insurance of risks of the work, the proposal of the mechanisms for the development of the Technical Management, the elaboration of directives of the Management of the Human Talent for the adoption of measures of control, that prioritize the protection of the insured and the employer, and develop an outline of the procedures and basic operational programs aimed at the prevention of occupational hazards. The research is developed in an organization located in Zone 8 of the Guayaquil Canton of the Guayas Province, with twenty years of experience in the market, dedicated to the design, construction, maintenance of infrastructures, specialized engineering services and other accessories, taking as measurement parameter the efficiency index (IE) of the Occupational Health and Safety Management System (SGSST) and the degree of perception that the insured and the employer have about its elements, for this it is necessary to strengthen the Management Administrative for the direction of the organization in the matter of prevention of risks of the general insurance of risks of the work, the This research project mainly proposes to design an SGSST for the prevention of risks of the work under the requirements of the Regulation of the General xi Insurance of Risks of the Work "Resolution No. CD513", the diagnosis of the current situation of the organization in relation to the general occupational risk insurance, which determines that it has several shortcomings in terms of the prevention of occupational risks, therefore the implementation of an SGSST is appropriate for the organization.